Blood in Eden - Tremayne, Peter (Tremayne, Peter. Sister Fidelma novels., 2019)
Ireland, AD 671. The hamlet of Cloichín is said to be a veritable Eden, with its prosperous farms and close-knit, friendly community. But after a local farmer, his wife and two sons are murdered, a fanatical new priest orders the villagers to lynch the man accused of the crime. The only evidence they hold against him is the fact that he is a stranger to their land. Searching for accommodation on their journey home to Cashel, Sister Fidelma and Eadulf arrive at Cloichín just in time to save the man's life. Fidelma is determined that the villagers must give the newcomer a fair trial. But there is to be more blood in Eden and more lives will be lost as long-standing friends become new-found enemies, and no one knows who to trust...